Pemberdayaan Pengrajin Batik Tasikmalaya Melalui Pemasaran Digital - Wiliana, Eneng; Purwaningsih, Nining; Apriyanti, Metha Dwi (Yayasan Daarul Huda Kruengmane, 2024)
The program to empower Tasikmalaya batik craftsmen through digital marketing is an initiative aimed at increasing the competitiveness and sustainability of the local batik industry in the digital era. Through a series of training, mentoring and field practice for six months, this program succeeded in increasing the digital literacy and online marketing abilities of craftsmen. Results show significant improvements in artisans' online presence, quality of digital content, and expansion of market reach. As many as 78% of participants succeeded in creating and managing business accounts on social media, while 65% already had active online shops on e-commerce platforms. There was an average increase of 35% in online sales and 28% in artisan income. This program also has an impact on strengthening the Tasikmalaya batik brand and product innovation based on digital feedback. Despite challenges in adapting to technology, the program demonstrates the significant potential of digital marketing in empowering traditional creative industries. Sustainability and further development of these achievements requires continued support and collaboration between craftsmen, local governments and other stakeholders.